The MSH2 c.793-1G>A variant disrupts normal splicing and is associated with Lynch syndrome - Li, Yiming; Yu, Lulu; Cui, Jiajia; Yin, Jiye; Wu, Wei (Frontiers in Oncology, 2023)
Lynch syndrome (LS) is the most common inherited cancer predisposition disorder of colorectal cancer (CRCs) which associated with pathogenic variants in 4 mismatch repair (MMR) genes. Here, we reported a multi-generation Chinese family clinically diagnosed with LS. To identify the underlying pathogenic gene variants for LS in this family, MSI testing and immunohistochemistry (IHC) revealed that MSI-H and MMR deficient. Whole-Exon Sequencing (WES) successfully identified a splicing variant (c.793-1G>A) in intron 4 of MSH2. Sanger sequencing validated the WES results and PCR identified all 'healthy' individuals carrying the variant. Bioinformatics analysis and in vitro minigene assay showed that the pathogenic variant affected the splicing process of MSH2 gene and consequently reduced expression of MSH2 protein. The mutation carriers were later recommended for colonoscopy and other important cancer diagnostic inspections every 1-2 years because they both have higher risk of LS. In conclusion, we found a novel splicing variant (rs863225397, c.793-1G>A) of MSH2 gene, and furtherly confirmed that this mutation plays an important role in LS patients of this pedigree based on the vitro study. Our study indicates that a novel splicing mutation in the MSH2 gene (c.793-1G>A) causes LS and highlights the importance of LS gene testing.